A Scenario-Based Land and Irrigation Capability Assessment for Crop Intensification- A Case Study of Jharkhand, Eastern India - R. Thakur, A.K. Singh (Journal of the Indian Society of Soil Science, 2017)
Land suitability evaluation is an important tool to detect extended use of land and water for crop intensification at farm scales. In the present study, a land suitability evaluation in Balpahari area of Jharkhand (India) was carried out in 39,854 ha area through close examination of the indicators of land suitability. Three scenarios were constructed such as, soil scenario to support variety of crop cultivation; crop scenario in which multiple cropping system lead to further increase in the cultivation area; and an irrigation scenario in which crops of dry season can be irrigated. The parameters taken into consideration were soil texture, depth, slope, surface flooding, drainage, pH, soil nitrogen (N), phosphorus (P), potassium (K) and crop-water requirement. Based on landform analysis, field surveys, laboratory analysis and field reviews, various thematic maps were prepared on 1:250,000 scale for scenario analysis of the study area. The effective rainfall and evapotranspiration of various crops were computed using the CROPWAT8.0 model. The study revealed the potential of soil and irrigation for increasing the crop area to enhance the livelihood support of small farmers. About 14,467 ha area were categorized as LCC-II where wide range of crops like vegetables, oilseeds and some pulse crops can be grown during winter and summer season with supply of life saving irrigation besides rice during rainy season. About 21,011 ha area were grouped under LCC-III and found suitable for short duration variety of mustard and potato with proper management of land, fertilizer and water. Crop rotation like rice-potato-green gram and rice-mustard-vegetables in low land, and maize-mustard-green manuring and black gram-lentil-green manuring in upland were suggested as most feasible cropping systems. This information is important for both, at farm level for farmers’ decision making on agricultural management, and at regional level for policy decision making on sustainability governance.